DETERMINASI KUALITAS SARANA-PRASARANA, KUALITAS DOSEN, DAN RELEVANSI KURIKULUM TERHADAP KEPUASAN MAHASISWA: STUDI EMPIRIS DI PROGRAM STUDI MANAJEMEN BISNIS INTERNASIONAL (MBI) INSTITUT SAINS DAN BISNIS INTERNASIONAL (ISBI) SINGKAWANG - Blikololong, Yohanes Gala Araftake; Saputra, Kasnur; sutarto, sutarto (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
ABSTRACT This study aims to examine the influence of facility quality, lecturer quality, and curriculum relevance on student satisfaction within the International Business Management (IBM) Study Program at the Institute of Science and International Business (ISBI) Singkawang. A quantitative associative approach was employed using a survey method. The population consisted of all active students in the IBM program, with a total sample of 25 respondents selected through purposive sampling, representing the entire population. The research instrument used was a Likert-scale questionnaire, which had previously undergone validity and reliability testing. Data were analyzed using multiple linear regression with IBM SPSS version 31. The classical assumption tests indicated that the data met the criteria for normality, linearity, absence of multicollinearity, and no heteroscedasticity. The regression analysis revealed that the three independent variables—facility quality (X?), lecturer quality (X?), and curriculum relevance (X?)—collectively exert a significant influence on student satisfaction (Y), as evidenced by a significance level of 0.001 (< 0.05) and an F-value of 419.655 (> F-table value of 3.07). Individually, each independent variable also demonstrated a significant effect, with curriculum relevance (X?) emerging as the most dominant factor, shown by the highest regression coefficient (B = 0.839) and the largest t-value (11.857). The coefficient of determination (R²) was found to be 0.984, indicating that 98.4% of the variance in student satisfaction can be explained by the three independent variables, while the remaining 1.6% is influenced by other factors outside the model. These findings highlight the critical role of enhancing curriculum relevance as a top priority in improving student satisfaction, while also emphasizing the importance of advancing both facility quality and lecturer competence within the IBM program at ISBI Singkawang. Keywords: facility quality, lecturer competence, curriculum relevance, student satisfaction, multiple linear regression, SPSS